2021
DOI: 10.4269/ajtmh.20-1516
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Contamination on the Household Compound and in Water Sources are Associated with Subsequent Diarrhea in Young Children in Urban Bangladesh (CHoBI7 Program)

Abstract: We investigated the environmental and individual-level risk factors for diarrheal disease among young children in slum areas of Dhaka, Bangladesh. A prospective cohort study was conducted among 884 children under 5 years of age. Caregiver reports were collected on sociodemographic factors and hygiene behaviors. Diarrhea surveillance data was collected monthly based on caregiver-reported diarrhea for children in the past 2 weeks during the 12-month study period. Unannounced spot checks of the household compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
(76 reference statements)
1
6
0
Order By: Relevance
“…57,58 In our study, the presence of feces on the ground of the household compound was associated with diarrhea in young children. This finding is consistent with that of our previous study in urban Bangladesh 17 and from a study in rural Ethiopia, 26 which found that presence of feces around the household compound was associated with greater odds of diarrhea. A previous study in Mozambique 59 also found that the presence of feces or soiled diapers on the household compound was associated with greater protozoan infections.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…57,58 In our study, the presence of feces on the ground of the household compound was associated with diarrhea in young children. This finding is consistent with that of our previous study in urban Bangladesh 17 and from a study in rural Ethiopia, 26 which found that presence of feces around the household compound was associated with greater odds of diarrhea. A previous study in Mozambique 59 also found that the presence of feces or soiled diapers on the household compound was associated with greater protozoan infections.…”
Section: Discussionsupporting
confidence: 92%
“…61 The association observed in our study is likely because feces in the household compound contaminated cooked food and drinking water. 17,23 Uncovered cooked food stored without refrigeration was associated significantly with subsequent diarrhea in young children. This is likely because uncovered food can be contaminated through flies and rodents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies reported a high prevalence of diarrhea in children of families with a low socio-economic status because of a reduced access to safe drinking water or proper toilets and sanitation facilities (Hubbard et al, 2020;Soboksa et al, 2021). The inaccessibility to safe drinking water refers to drinking water contamination with the fecal material, and the presence of fecal material in the drinking water reflects the presence of enteropathogens, which are responsible for various types of enteric diseases, including diarrhea, typhoid, cholera, and others (Loyola et al, 2020;Parvin et al, 2021). Similarly, the use of shared toilet facilities and unimproved toilet facilities also increased the odds of diarrheal and enteric diseases in children (Hubbard et al, 2020;Ishimwe et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Pollution due to the disposal of the contents of the feces storage tank results in the presence of feces around the house and sources of drinking water. Both of these are significant risk factors for the occurrence of infectious diseases such as diarrhea, especially in children under 5 years of age [9]. The contents of the feces storage tank pollute the environment, one of which is the water source used by the community.…”
Section: Results and Discussion Assessment Of Domestic Wastewater Par...mentioning
confidence: 99%